The potential of grafting with selected stone fruit varieties for management of almond witches’ broom - Patil TAWIDIAN; Maan JAWHARI; Hana SOBH; Piero BIANCO; Yusuf ABOU-JAWDAH (Phytopathologia Mediterranea, 2018)
A lethal disease of stone fruit trees, characterized by proliferation of axillary shoots and witches’ broom symptoms, has caused severe problems for more than 200,000 almond, peach and nectarine plants in Lebanon since the 1990s. The agent associated with almond witches’ broom (AlmWB) was identified as ‘Candidatus Phytoplasma phoenicium’, belonging to subgroup 16SrIX-B. Management of the disease has relied on uprooting of affected trees. Since no disease-resistant cultivars have been identified, grafting experiments in the field and in the greenhouse we performed to develop a new option for the integrated management of the disease. AlmWB-affected almond trees were grafted with apricot or plum scions, and their growth was symptomless for over 2 years in the field. Similarly, in greenhouse trials, grafting AlmWB-affected almond scions onto seedlings of plum and apricot resulted in growth of symptomless shoots. One year post-grafting in the greenhouse the phytoplasma was not detected by PCR in almond grafted on Angeleno and Red plum and Early Blush apricot used as rootstocks. The phytoplasma was, however, detected in almond scions grafted on Farclo apricot and Jawhara plum, although their growth was symptomless. Shoots developing from Farclo apricot grafted on AlmWB-affected trees in the field showed severe symptoms 2 months after grafting but recovered 3 months later, and remained symptomless for about 2.5 years. Similarly, in the greenhouse trial, the growth of phytoplasma-infected scions grafted on Early blush apricot developed symptoms 2 months after grafting, did not show symptoms 2 months later, and remained symptomless 1 year later. Quantitative PCR analysis of almond scions grafted on Early blush apricot seedlings confirmed reduction of phytoplasma titre from 44 GU/ng DNA to below detection level.